Inventorying the tree fern Genus Cibotium of Sumatra: Ecology, population size and distribution in North Sumatra - TITIEN NGATINEM PRAPTOSUWIRYO; DIDIT OKTA PRIBADI; DWI MURTI PUSPITANINGTYAS; SRI HARTINI (Biodiversitas Journal of Biological Diversity, 2011)
Praptosuwiryo TNg, Pribadi DO, Puspitaningtyas DM, Hartini S (2011) Inventorying the tree fern Genus Cibotium of Sumatra: Ecology, population size and distribution in North Sumatra. Biodiversitas 12: 204-211. Cibotium is one tree fern belongs to the family Cibotiaceae which is easily differentiated from the other genus by the long slender golden yellowish-brown smooth hairs covered its rhizome and basal stipe with marginal sori at the ends of veins protected by two indusia forming a small cup round the receptacle of the sorus. It has been recognized as material for both traditional and modern medicines in China, Europe, Japan and Southeast Asia. Population of Cibotium species in several countries has decreased rapidly because of over exploitation and there is no artificial cultivation until now. The aims of this study were: (i) To re-inventory the species of Cibotiun in North Sumatra, (ii) to record the ecology and distribution of each species, and (iii) to assess the population size of each species. Field study was carried out by using random search with belt transect. Two species were recorded, namely C. arachnoideum dan C. barometz. The geographical distribution of the two species in North Sumatra is presented. Cibotium is commonly growing terrestrially on opened or rather opened areas in secondary forest and primary forest at hills or lower mountains with a relatively high humidity at 30-90Âº slopes. C. arachnoideum has a strict distribution and only found at 1740-1770 m a.s.l. in primary forest, whereas C. barometz has a broad distribution in secondary forest at elevation range from 650-1200 m.